Reemigracja polskich górników z Rumunii na Górny Śląsk po II wojnie światowej - Nowak, Krzysztof (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
In 1946–1948, the Polish authorities made efforts to encourage the re-emmigration of Polish miners with their families from Lupeni in Romanian Transylvania, who were descendants of 19 th-century economic emigrants from Galicia. These activities were mainly carried out by the Central Board of the Coal Industry in Katowice, reporting to the Ministry of Industry. After arduous negotiations with the Romanian authorities, over 600 people came to Poland from Lupeni and settled in Kędzierzyn.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne